Effective incineration of fuel-waste slurries from several related industries; Environmental Research; Vol. 176 - Nyashina G. S. Galina Sergeevna; Vershinina K. Yu. Kseniya Yurievna; Shlegel N. E. Nikita Evgenjevich; Strizhak P. A. Pavel Alexandrovich (2019, 2019)
Title screen